2007
DOI: 10.1002/adma.200700149
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Thermal Organogel

Abstract: Organogels have been extensively studied during the last decade because of their potential as an oil-recovery medium, sensors, media for electrochemistry, templates for the fabrication of nanostructures, drug-delivery, and rheological modifiers, as well as because of their interesting supramolecular assembly patterns. [1][2][3][4][5] Typically, the gel-forming material, called an organogelator, has marginal solubility in organic solvents because of the presence of a solubilizing alkyl group and strongly intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…19,20 The molecular weight of the polymer was determined by the peak area at 3.7-4.1 ppm (-CH 2 CH 2 O) and 1.5-2.0 ppm (-COCH(CH 3 )NH-) in 1 H-NMR (CF 3 COOD). The molecular weights of the polymers were 1710 ((EG) 21 -(A) 10 ) and 1780 ((EG) 21 -(A) 11 ) for mPEG-L-PA and mPEG-DL-PA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 The molecular weight of the polymer was determined by the peak area at 3.7-4.1 ppm (-CH 2 CH 2 O) and 1.5-2.0 ppm (-COCH(CH 3 )NH-) in 1 H-NMR (CF 3 COOD). The molecular weights of the polymers were 1710 ((EG) 21 -(A) 10 ) and 1780 ((EG) 21 -(A) 11 ) for mPEG-L-PA and mPEG-DL-PA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 To prepare mPEG-L-PA, a-methoxy, u-amino poly(ethylene glycol) (2.5 g, 2.5 mmole; MW 1,000 daltons) was dissolved in anhydrous toluene (50 mL) and the residual water was removed by azeotropic distillation to a final volume of about 5 mL. Anhydrous chloroform/N,Ndimethyl formide (30 mL; 2/1 v/v), N-carboxy anhydrides of L-alanine (4.0 g, 34.8 mmole) were added to the reaction mixtures.…”
Section: Synthesis Of the Mpeg-l/or Dl-pamentioning
confidence: 97%
“…Tang et al [28] observed gelation for aqueous solutions of PMMA-b-PNIPAM induced by aggregation of the PNIPAM corona above its critical temperature. Similarly Jeong et al [29] observed gelation of PEO-bpoly(L-alanine-co-L-phenylalanine) in chloroform with increasing temperature due to the increasing attractions between the PEO coronas. Grandjean et al [30] studied the aggregation and gelation of PS-P(AA/EA) in water and found that attraction between the coronas increased if they contained a larger fraction of EA.…”
Section: Polymers With a Single Associative Block (A-b Or A-b-a)mentioning
confidence: 94%
“…When the PEG-polypeptide was dissolved in chloroform, the polymer solution also underwent sol-to-gel transition as the temperature increased. 78,79 The desolvation of the chloroform from the PEG is responsible for the transition. When the polypeptides have a mixed conformation of -sheets and -helixes in chloroform, the gel morphology tends to be a spherical micelles or short tubular structure, whereas the gel morphology tends to be a fibrous structure when the polypeptides dominantly form a -sheet conformation in chloroform.…”
Section: Polypeptidesmentioning
confidence: 99%